2021
DOI: 10.1136/bmjopen-2020-047832
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from countries implementing find, test, trace, isolation and support policies in the rapid response of the COVID-19 pandemic: a systematic review

Abstract: ObjectiveTo systematically learn lessons from the experiences of countries implementing find, test, trace, isolate, support (FTTIS) in the first wave of the COVID-19 pandemic.Design, data sources and eligibility criteriaWe searched MEDLINE (PubMed), Cochrane Library, SCOPUS and JSTOR, initially between 31 May 2019 and 21 January 2021. Research articles and reviews on the use of contact tracing, testing, self-isolation and quarantine for COVID-19 management were included in the review.Data extraction and synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 109 publications
0
42
0
Order By: Relevance
“…The latter phenomenon was revealed in other territories as well [13]. The desire to break this connection is precisely what caused the widespread use of self-isolation regimes in Belarus [22,24,26]. It can be assumed that the nature of the relationship between population density and morbidity is, to some extent, due to the late introduction of restrictive antiepidemic measures to protect the population from SARS-CoV-2 [39].…”
Section: Figure 4 Correlation Between Morbidity Rate and Population Densitymentioning
confidence: 99%
“…The latter phenomenon was revealed in other territories as well [13]. The desire to break this connection is precisely what caused the widespread use of self-isolation regimes in Belarus [22,24,26]. It can be assumed that the nature of the relationship between population density and morbidity is, to some extent, due to the late introduction of restrictive antiepidemic measures to protect the population from SARS-CoV-2 [39].…”
Section: Figure 4 Correlation Between Morbidity Rate and Population Densitymentioning
confidence: 99%
“…Countries or cities with a high population density and aged population including Hong Kong is at risk of severe outbreak of emerging infectious diseases such as COVID-19 [ 20 ]. As the disease is spreading rapidly in multiple continents, many countries implemented border restrictions towards regions with severe outbreak in order to reduce local case number and mortality [ 20 – 22 ]. This is particularly important for developing countries with inadequate medical resources to tackle massive local outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies on testing and screening uptakeincluding for COVID-19 -have reported associations between the number of test sites or test site vicinity, and test uptake. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Much of this evidence is from low-resource settings or underserved population in high-income settings. One experimental study on screening for HIV reported observing an effect for test site vicinity as close as 1.5 kilometres in a low-income context.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 One reason people self-report for not getting tested is a lack of accessibility to (free) testing sites. [6][7][8][9] Prior to the COVID-19 pandemic, studies have considered proximity of testing sites in various health contexts, such as for HIV, STI, cognitive impairment, TB and cancer screenings. Mostly, studies rely on surveying self-reported barriers or use geographical mapping to examine test-uptake by looking at the distance between test site and people's home address.…”
Section: Introductionmentioning
confidence: 99%